Endocrown as an alternative to rehabilitate endodontic teeth. Case report - Mora Torres, Josué Alexander (2021)
The objective of this study is to restore, through the occlusal plane, the aesthetics and functionality of a piece treated endodontically in the posterior sector through an endo-crown. The following case is a 27-year-old male patient with no relevant medical history who attended the SERODU dental clinic. The radiographic examination revealed the endodontic canals, which were protected by a cavity base and provisional filling. The intraoral examination revealed that tooth number 46 lost the distal wall and part of the palatine, so it was decided to carry out the rehabilitation with an endo-crown, as it has a good hermetic seal at the coronal level, it prevents possible re-contamination of the treatment endodontic resulting in a conservative and feasible alternative.